Denial of Dalit Agency in V.S. Pamar's "Bap Nu Barmu" - Binadi, Chet Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
This paper attempts to study the denial of Dalit agency in "Bap Nu Barmu", a short story by V.S. Parmar where the major character Amrut's condition is portrayed highly sympathetic and devoid of true agency in the society ordained in the theolological structure of caste based hierarchy. He belongs to Dalit community and is structured by fragmented self in the social spectrum based on the hierarchical schematization. He cannot develop emancipatory mode of thinking though he is a university degree holder; and remains crushed under the obligations of social tradition, remains muted, devoid of agency and true self in every events of the story. By representing the hardship of Amrut in this story, the writer foregrounds the real situation of Dalit subaltern of the then time and throws light on the hegemonic exception of caste system which hinders the true resistance against every kinds of subjugation imposed on Dalit community as a part of caste based society. This study tries to unearth the agency of Dalit subjectivity and inner freedom by using the theoretical tenets of Antonio Gramsci, Spivak and Michael Garnett.